EARLY GLYCOTOXIN EXPOSURE INDUCES EX-VIVO LEFT VENTRICULAR DYSFUNCTION IN ADULT RATS (Arquivos do Mudi, 2023)
The exposure of the fetus/neonate to glycotoxins via the placenta or breast milk, such as themethylglyoxal (MG), has been related to short- and long-term disorders in its development.The aim of this study was to evaluate the effects of early exposure to methylglyoxal, duringthe lactation phase, on cardiac parameters at adulthood. All the experimental procedures wereapproved by the ethics committee of animal use of UFG (007/21). Eight pregnant rats wereseparated into: vehicle group (VEH); and MG group, MG (60 mg/kg), the treatment wascarried out from PN3 to PN14. The litters were standardized 4 male and 4 female pups. AtPN120, hearts were mounted in a Langendorff apparatus. 10’ of basal, 30’ ischemia and 30’of reperfusion were performed. Intraventricular systolic (ISP) and diastolic (IDP) pressure,dP/dt + and - were recorded. AUC of each experiment was calculated, and the results werecompared using two-way ANOVA with Sidak’s post-hoc test. Despite of no difference in theheart-to-body weight ratio, MG hearts presented reduced basal LV contractility in both male(p<0.01) and female (p<0.01) offspring. After ischemia, MG groups still presented decreasedLV contractility in both male and female offspring (p<0.05). Glycotoxins exposure during thelactation leads to reduced intrinsic contractility at adulthood and reduced chances of survivingischemic events.